THE FOSSIL WOOD OF TAXODIACEAE FROM THE ALBIAN DEPOSITS OF THE KANEV OUTSKIRTS - Popova, L.; Moroz, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
New finding of the fossil wood with the rings in the Albian deposits of the Kanev outskirts allows to suggest increasing of the cli-matic factor influence due to decreasing of the edaphic one. It is likely that the specimen was growing under the conditions of abrasive slope or elevated area with thin soils.